Analysis of Determinants of Return on Assets at DKI Jakarta Regional Development Bank Using the Partial Adjustment Model - Edi Supriyono (KENDALI: Economics and Social Humanities, 2025)
This study aims to analyze the factors that affect the Return on Assets (ROA) at the Jakarta Regional Development Bank (BPD) using the Partial Adjustment Model (PAM) approach during the 2017–2024 period. The independent variables used include Operating Expenses to Operating Income (BOPO), Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Minimum Mandatory Current Account (GWM), and ROA for the previous period (ROA (-1)) as a form of partial adjustment. The estimated results showed that BOPO had a significant negative effect on ROA, while NPL, LDR, and ROA (-1) had a significant positive effect. The reserve requirement does not have a significant influence on ROA. The model passed the test of classical assumptions, including normality, multicollinearity, heteroscedasticity, and autocorrelation, which strengthened the reliability of the results. These findings indicate that operational efficiency and credit risk management strategies are the main keys in increasing the profitability of BPD DKI Jakarta. This research provides important implications for bank management and banking authorities in formulating more effective and sustainable data-based policies.